A COMPARATIVE STUDY OF BANKING EFFICIENCY IN ASEAN-5: THE DATA ENVELOPMENT ANALYSIS (DEA) APPROACH - Setyo Tri Wahyudi; Azizah Azizah (Faculty of Economics and Business, Universitas Gadjah Mada, 2018)
As an intermediary institution, a bank is required to operate efficiently due to the increased competition among banks, both domestic and international. However, not all banks are able to optimize their owned resources to reach a certain efficiency level. Thus, efficiency plays an important role in this era of more globalized banking competiti on. The objective of this study is to calculate the banking efficiency score for the ASEAN-5 countries, consisting of Indonesia, Malaysia, the Philippines, Singapore, and Thailand. Using Data Envelopment Analysis (DEA), the input variables comprised of employees’ benefits, fixed assets, and deposits; while the output variables were total income and loans. The results show the relatively high efficiency levels of every bank in each country. The achievement of an input-output efficiency variable in the first period (2006-2009) tended to increase, but the second period (2010-2013) showed a declining trend. The performance of the banks in Singapore during the first period was very good, while in the second period, the banks in the Philippines showed a respectable performance.